The role of performance measurement during product design & development in a manufacturing environment - Driva, Helen (1997)
Effectively managing and measuring the product development process is widely seen as a means of ensuring business survival through reduced time to market, increased quality and reduced costs. This thesis explores the research question of "How do companies know that they are making effective use of their product design and development function?".